2018
DOI: 10.1186/s13059-018-1551-9
|View full text |Cite
|
Sign up to set email alerts
|

Alternative polyadenylation factors link cell cycle to migration

Abstract: BackgroundIn response to a wound, fibroblasts are activated to migrate toward the wound, to proliferate and to contribute to the wound healing process. We hypothesize that changes in pre-mRNA processing occurring as fibroblasts enter the proliferative cell cycle are also important for promoting their migration.ResultsRNA sequencing of fibroblasts induced into quiescence by contact inhibition reveals downregulation of genes involved in mRNA processing, including splicing and cleavage and polyadenylation factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 113 publications
(140 reference statements)
3
31
0
Order By: Relevance
“…An asymmetric pattern of IR change has also been associated with changes in cellular state. For example, differentiated and quiescent cells have higher IR levels compared to proliferating cells 48,[75][76][77] . In yeast, intron retention in the Gcr transcription factor has been associated with changes in nutrient status and the isoforms with and without the intron were both required for expression of target genes involved in glycolysis 78 .…”
Section: Discussionmentioning
confidence: 99%
“…An asymmetric pattern of IR change has also been associated with changes in cellular state. For example, differentiated and quiescent cells have higher IR levels compared to proliferating cells 48,[75][76][77] . In yeast, intron retention in the Gcr transcription factor has been associated with changes in nutrient status and the isoforms with and without the intron were both required for expression of target genes involved in glycolysis 78 .…”
Section: Discussionmentioning
confidence: 99%
“…APA has recently been identified as a candidate driver of gene expression dysregulation. APA factors frequently show aberrant expression in cancer, modulate the expression of known oncogenes and tumor suppressors, and knockdown studies have highlighted their relevance to the cancer phenotype 3134,102,103 . Whole-genome CRISPR and shRNA screens have also revealed the requirement for several APA factors in pancreatic cancer cell growth (www.depmap.org).…”
Section: Discussionmentioning
confidence: 99%
“…4). CSTF2 has previously been implicated as a promoter of lung and bladder cancer, through the regulation of ERBB2 and RAC1 3’-UTRs, respectively 33,34 . We find frequent 3’-UTR alterations in several notable PDA-relevant genes whose mechanisms of regulation were previously unknown, including PAF1 , ALDOA and FLNA .…”
Section: Discussionmentioning
confidence: 99%
“…CFIm25 is known to be crucial in controlling invasion and metastasis of HCC 32 . It is also confirmed that www.nature.com/scientificreports/ activation of APA sites can affect the migratory capacity of cancer cells 33 as well as fibroblasts 34 . According to the results of wound healing assay, regulation of CFIm25 expression by miR-23 and 374 directly controls breast cancer cells' migration and invasion.…”
Section: Discussionmentioning
confidence: 62%